Prognostic factors for donor lymphocyte infusions following non-myeloablative allogeneic stem cell transplantation in multiple myeloma - Donk, Niels van de; Kröger, N.; Hegenbart, Ute; Corradini, P.; Miguel, J. F. San; Goldschmidt, Hartmut; Perez-Simon, J. A.; Zijlmans, M.; Raymakers, R. A.; Montefusco, V.; Ayuk, F. A.; van Oers, M. H. J.; et al. (Bone marrow transplantation, 2006)
In this retrospective study, we evaluated donor lymphocyte infusions given for relapsed (n=48) or persistent (n=15) myeloma following non-myeloablative allogeneic stem cell transplantation (Allo-SCT). Twenty-four of 63 patients (38.1%) responded: 12 patients (19.0%) with a partial response (PR) and 12 patients (19.0%) with a complete response (CR). Overall survival after donor lymphocyte infusions (DLI) was 23.6 months (1.0-50.7+). Median overall survival for non-responding patients was 23.6 months and has not been reached for the patients responding to DLI. In responders, progression-free survival after DLI was 27.8 months (1.2-46.2+). Patients with a PR had a median progression-free survival of 7.0 months, whereas patients with a CR to DLI had a median progression-free survival of 27.8 months. Major toxicities were acute graft-versus-host disease (GVHD) (38.1%) and chronic GVHD (42.9%). Seven patients (11.1%) died from treatment-related mortality. The only significant prognostic factors for response to DLI were the occurrence of acute and chronic GVHD. There was a trend towards significance for time between transplantation and DLI, and response. Donor lymphocyte infusion following non-myeloablative Allo-SCT is a valuable strategy for relapsed or persistent disease.